UMP appointed by Mara to conduct halal gelatine project - Laila, Zulkepele (Penerbit UMP, 2015)
Universiti Malaysia Pahang (UMP) was appointed by federal agency Majlis Amanah Rakyat (MARA) to carry out a halal gelatine production project worth RM20 million at ITECS, UMP Pekan.